Static loading for protective cabs and frames for agriculture wheele tractors, including acceptance conditions - British Standards Institution (London BSI, 1985)
Tractors, Agricultural tractors, Forestry equipment, Protective cabs, Cabs, Transportation safety, Safety devices, Roll-over protective structures, Overturning, Static loading, Mechanical testing, Framed structures, Acceptance (approval), Crushing tests, Specimen preparation, Clearances, Tolerances (measurement), Marking, Brittleness, Fracture, Impact strength, Low temperatures
Revised, Withdrawn
Cross References BS 4063, ISO 612
Replaced By BS 5947:1992, ISO 5700:1989
Keywords: Agricultural tractors -- Standards